2013
DOI: 10.5114/wo.2013.35684
|View full text |Cite
|
Sign up to set email alerts
|

Reviews Basal cell carcinoma – diagnosis

Abstract: Basal cell carcinoma is the most common skin cancer in the Caucasian population. The cancer arises in sun exposed areas of the skin. The incidence of morbidity is high and it is still growing. The metastatic rate is low, but the enlarging tumor may cause severe tissue disfigurement and a poor cosmetic outcome. The diagnosis is usually clinical but there are many subtypes of this carcinoma and correct diagnosis is the clue to appropriate treatment of the lesion. The main problem in basal cell carcinoma manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 30 publications
0
66
0
1
Order By: Relevance
“…It has been suggested that this feature stems from peritumoral mucin; from peritumoral oedema or cellular peripheral palisading of BCC cells (accumulation of elongated nuclei orientated in the same axis) . It might be that the OCT finding is associated with all three suggestions; however, in the histological literature, the absence of peripheral palisading and retraction is often described in iBCC subtypes and has generally been associated with more aggressive BCC subtypes . Regardless of the origin of this feature, DPB in OCT images seems to be an important in vivo OCT characteristic for differentiating iBCC aggressive subtypes from sBCC and nBCC.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that this feature stems from peritumoral mucin; from peritumoral oedema or cellular peripheral palisading of BCC cells (accumulation of elongated nuclei orientated in the same axis) . It might be that the OCT finding is associated with all three suggestions; however, in the histological literature, the absence of peripheral palisading and retraction is often described in iBCC subtypes and has generally been associated with more aggressive BCC subtypes . Regardless of the origin of this feature, DPB in OCT images seems to be an important in vivo OCT characteristic for differentiating iBCC aggressive subtypes from sBCC and nBCC.…”
Section: Discussionmentioning
confidence: 95%
“…There are three main histological subtypes of BCC, namely, nodular, superficial, and infiltrative (including morpheaform), although tumors may present a combination of at least two of the aforementioned subtypes; in this case, they are classified as mixed tumors (Rippey, ). The infiltrative/morpheaform subtypes and the micronodular variant of the nodular BCC are considered more aggressive (Mackiewicz‐Wysocka, Bowszyc‐Dmochowska, Strzelecka‐Węklar, Dańczak‐Pazdrowska, & Adamski, ).…”
Section: Histological Featuresmentioning
confidence: 99%
“…This prevalence is projected to increase twice in every 25 years, with the ratio becoming 3:2 [4]. Most BCCs are located on the upper parts of the body, with 75-80% located on the face making BCC although only locally destructive cosmetically damaging [5–7]. …”
Section: Introductionmentioning
confidence: 99%